Preparation method of oxygen-rich defect nano-zinc oxide particles and catalyst thereof
By using specific precursor solutions and high-temperature treatment methods in the preparation of zinc oxide catalysts, oxygen-rich nano zinc oxide particles were successfully prepared, solving the problems of large particle size, complex preparation and high cost in the prior art, and achieving efficient automotive exhaust purification.
Patent Information
- Application Number
- CN202311425466.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing methods for preparing zinc oxide catalysts have resulted in large sizes of zinc oxide particles, complex preparation process and high cost, and are not suitable for large-scale industrial production.
The zinc salt, diamine organic matter and dicarboxylic acid are dissolved in deionized water to form a zinc-containing precursor solution. After heating, centrifugation, washing and drying, it is heated to 500°C to 800°C under an inert atmosphere or vacuum condition to prepare oxygen-rich nano zinc oxide particles.
The prepared oxygen-rich nano zinc oxide particles have a small size and low cost, which are suitable for large-scale industrial production. Due to the existence of oxygen-rich defects, palladium atoms are activated and the catalytic activity of automobile exhaust purification is improved.
Smart Images

Figure CN119909668A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to automobile exhaust purification technology, and in particular to a preparation method of oxygen-rich defect nano zinc oxide particles and a catalyst thereof. Background Art
[0002] Air pollution is one of the main environmental pollutions, and automobile exhaust accounts for more than 60% of air pollutants. It is an important problem that needs to be solved urgently. Automobile exhaust pollution control generally adopts automobile exhaust catalytic purification technology.
[0003] Nano zinc oxide is a new type of functional fine chemical material. It has the characteristics of high stability, good thermal and optical properties, strong antibacterial properties and excellent catalytic properties. It is widely used in the fields of catalysts, optoelectronics, food industry and daily chemical industry. The activity of the catalyst with nano zinc oxide as the carrier is linearly related to the temperature, and the purification rate of pollutants is higher at 300°C. However, when the car is just starting, the activity of this type of catalyst is extremely low, resulting in its purification rate not being able to effectively purify the car exhaust.
[0004] Numerous experiments have shown that by introducing defects and adjusting the electronic structure of zinc oxide, the photocatalytic and thermal catalytic capabilities of zinc oxide can be greatly improved. The Chinese invention patent with publication number CN 113582218 A discloses an oxygen-deficient gray zinc oxide and its preparation method and application, wherein lithium and naphthalene are dissolved in a solvent to obtain a lithium naphthalene solution, white zinc oxide is added to the obtained lithium naphthalene solution for reaction, and solid products are collected after the reaction is completed, and the obtained solid products are washed and dried to obtain oxygen-deficient gray zinc oxide. However, the zinc oxide obtained by the preparation method is large in size, and the preparation process is relatively complicated and costly, which is not suitable for large-scale industrial production. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing oxygen-defect nano zinc oxide particles and a catalyst thereof, so as to solve the technical problems that the zinc oxide prepared by the existing preparation method is large in size, the preparation process is relatively complex, the cost is high, and it is not suitable for large-scale production.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing oxygen-defect nano zinc oxide particles, which is special in that it comprises the following steps:
[0008] Step 1, dissolving zinc salt, diamine organic matter and dicarboxylic acid in deionized water in sequence to obtain a zinc-containing precursor solution; the molar ratio of the zinc salt, diamine organic matter and dicarboxylic acid is 1:(0.5-2):(1.5-3); the mass ratio of the volume of the deionized water to the zinc salt is (1.25-5):1L / g;
[0009] Step 2, heating the zinc-containing precursor solution obtained in step 1 to 100-200° C. and keeping the temperature for more than 6 hours to obtain a reaction solution, and then centrifuging, washing, and drying the reaction solution in sequence to obtain zinc-containing metal organic framework solid particles;
[0010] Step 3, heating the zinc-containing metal organic framework solid particles obtained in step 2 to 500° C. to 800° C. in an inert atmosphere or vacuum condition, and keeping the temperature for more than 30 minutes to obtain oxygen-defect nano zinc oxide particles.
[0011] The reaction temperature here directly affects the amount of oxygen defects, and is generally selected to be 500-800°C. If the temperature is too low, defective zinc oxide cannot be formed. If the temperature is too high, the particle size of the defective zinc oxide finally obtained is too large.
[0012] Further, in step 1, the zinc salt is any one of zinc fluoride, zinc chloride, zinc bromide, zinc sulfate, zinc oxide, zinc sulfide or zinc nitride;
[0013] The diamine organic compound is any one of ethylenediamine, diethylenediamine, propylenediamine, dipropylenediamine or butanediamine;
[0014] The dicarboxylic acid is any one of oxalic acid, malonic acid or acetic anhydride.
[0015] Furthermore, in step 2, the insulation time is 6 to 48 hours;
[0016] The centrifugation is performed by a centrifugal device with a rotation speed of 5000 to 10000 rpm;
[0017] The washing is performed at least three times using deionized water with a purity of more than 99%.
[0018] Furthermore, in step 3, the gas in the inert atmosphere is argon or nitrogen with a purity of more than 99%;
[0019] The vacuum condition is air with a vacuum degree of ≤1 bar;
[0020] The insulation time is 30 minutes to 48 hours.
[0021] In addition, the present invention also provides a method for preparing an oxygen-defective nano zinc oxide particle catalyst, which is special in that it comprises the following steps:
[0022] Step 1, preparing oxygen-rich defect nano zinc oxide particles according to the above preparation method;
[0023] Step 2, weighing a palladium salt and mixing it with the oxygen-deficient nano zinc oxide particles prepared in step 1 to obtain a palladium-based precursor salt; the palladium loading in the palladium-based precursor salt is 1 to 10 wt%;
[0024] Step 3, dissolving a palladium-based precursor salt in a polyol solvent to obtain a palladium-based precursor solution; the mass ratio of the volume of the polyol solvent to the oxygen-defective nano zinc oxide particles is (0.1-1): 1 L / g;
[0025] Step 4, heating the palladium-based precursor solution to 220-250° C. and keeping the temperature for more than 10 minutes, and then centrifuging, washing, and drying in sequence to obtain an oxygen-defective nano zinc oxide particle catalyst.
[0026] Furthermore, in step 2, the palladium salt is any one of potassium hexachloropalladium IV acid, potassium hexachloropalladium IV acid, potassium tetrachloropalladium II acid, sodium hexachloropalladium IV acid, sodium tetrachloropalladium II acid or acetylacetonate palladium II.
[0027] Furthermore, in step 3, the polyol solvent is selected from any one of diethylene glycol, pentanol, hexanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butylene glycol, dibutylene glycol or tributylene glycol with a volume concentration of more than 99%.
[0028] Furthermore, in step 4, the insulation time is 10 to 30 minutes;
[0029] The centrifugation is performed by a centrifugal device with a rotation speed of 5000 to 10000 rpm;
[0030] The washing is performed using ethyl acetate with a purity of more than 99% and petroleum ether with a purity of more than 99% in sequence, and the washing is performed at least 3 times;
[0031] The drying temperature is 55-65° C. and the drying time is 10-15 hours.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The preparation method of the oxygen-rich defect nano zinc oxide particles of the present invention has relatively simple raw material selection, preparation conditions and specific operation process, and has low cost. At the same time, the oxygen-rich defect nano zinc oxide particles prepared by this method are small in size and have strong practicality.
[0034] 2. The preparation method of the oxygen-defect nano zinc oxide particle catalyst of the present invention has a simple operation process and low cost, so large-scale industrial production of such catalysts can be achieved based on this method.
[0035] 3. The oxygen-defective nano zinc oxide particles prepared by the present invention utilize the characteristics of the larger distance between zinc ions and the smaller overall framework density in the zinc-containing metal organic framework (zinc-containing MOF), so the particle size is smaller than that obtained by the prior art.
[0036] 4. The oxygen-defect nano zinc oxide particles prepared by the present invention can activate palladium atoms due to the interaction between a large number of unpaired electrons generated by the oxygen-defect and the loaded metal palladium, thereby obtaining a catalyst with higher automobile exhaust purification activity.
[0037] 5. The oxygen-defective nano zinc oxide particle catalyst prepared by the present invention has better performance in purifying automobile exhaust gas than the existing catalysts with aluminum oxide, zinc oxide, titanium oxide and other materials as carriers, and can therefore replace traditional catalysts for automobile exhaust gas purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a structural reference diagram for conducting a catalytic purification test of automobile exhaust using the catalyst prepared by the present invention.
[0039] Figure 2 This is the XRD spectrum of the oxygen-deficient nano zinc oxide particles obtained in Example 1 of the present invention.
[0040] Figure 3 This is the XRD spectrum of the oxygen-deficient nano zinc oxide particles obtained in Example 2 of the present invention.
[0041] Figure 4 This is the XRD spectrum of the oxygen-deficient nano zinc oxide particles obtained in Example 3 of the present invention.
[0042] Figure 5 The oxygen-defective nano zinc oxide particle catalyst obtained in Example 4 of the present invention is used to catalyze and purify NO from automobile exhaust x Conversion rate curve diagram.
[0043] Figure 6 The oxygen-defective nano zinc oxide particle catalyst obtained in Example 5 of the present invention is used to catalyze and purify NO from automobile exhaust x Conversion rate curve diagram.
[0044] Figure 7 The oxygen-defective nano zinc oxide particle catalyst obtained in Example 6 of the present invention is used to catalyze and purify NO from automobile exhaust x Conversion rate curve diagram.
[0045] Figure 8 The alumina-supported catalyst obtained in Comparative Example 1 of the present invention is used to catalytically purify NO from automobile exhaust x Conversion rate curve
[0046] Fig. 9 for Figure 5 , Figure 6 , Figure 7 , Figure 8 Medium NO x Conversion rate curve comparison chart.
[0047] Fig.10 This is the XRD spectrum of nano zinc oxide obtained in Comparative Example 2 of the present invention.
[0048] Fig.11 This is the XRD spectrum of nano zinc oxide obtained in Comparative Example 3 of the present invention.
[0049] Fig.12 This is the XPS spectrum of the oxygen-defective nano zinc oxide particles obtained in Example 1 of the present invention.
[0050] Fig.13 This is a comparison chart of the EPR spectra of the oxygen-defective nano zinc oxide particles obtained in Example 1 of the present invention and the defect-free nano zinc oxide material obtained in Comparative Example 2. DETAILED DESCRIPTION
[0051] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments to help those skilled in the art to have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention. It should be noted that, if specific conditions are not specified in the embodiments or comparative examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0052] The protection scope of the present invention includes but is not limited to the following embodiments. Without departing from the spirit and scope of the present invention, any modification made to the details and form of the technical solution of the present invention shall fall within the protection scope of the present invention.
[0053] The present invention uses low-priced raw materials to prepare oxygen-defect nano zinc oxide particles. According to calculations, it only costs 2.503 yuan to produce 1g of oxygen-defect nano zinc oxide particles: the lowest price of zinc compounds on the market is 16 yuan / kg, the lowest price of diamine organic matter used is 2.5 yuan / g, the lowest price of dicarboxylic acid used is 2.6 yuan / kg, and the process cost is 12 yuan / kg. The comprehensive cost is low, suitable for large-scale industrial production, and has good practicality. The oxygen-defect nano zinc oxide particles prepared by the present invention utilize the characteristics of large distances between zinc ions and small overall framework density in zinc-containing metal organic frameworks (zinc-containing MOFs), so the particle size is smaller, and the minimum can be as small as 8.1nm.
[0054] Example 1
[0055] A method for preparing oxygen-rich defective nano zinc oxide particles comprises the following steps:
[0056] Step 1: 814 mg of zinc oxide, 2.52 g of oxalic acid dihydrate and 1 mL of 1,4-diamine are dissolved in 10 mL of deionized water in sequence, and mixed evenly to prepare 11 mL of a zinc-containing precursor solution.
[0057] Step 2: Heat the zinc-containing precursor solution to 130° C. in a sealed environment for 24 hours, and the insulation process is the reaction process. Centrifuge at 8000 rpm to obtain a crude product, wash the crude product four times with 20 mL of deionized water, and dry to obtain 2.28 g of zinc-containing metal organic framework (i.e., zinc-containing MOF) solid particles.
[0058] Step 3, placing the zinc-containing MOF solid particles obtained in step 2 in a tubular furnace preheated to 550°C, and maintaining the vacuum degree in the tubular furnace above 0.99 bar, and keeping the reaction warm for 1 hour to obtain 812 mg of oxygen-defective nano zinc oxide particles. Table 1 shows that after the zinc oxide particles are treated with TOPAS3, the crystal size obtained is 8.1 nm, which is relatively small.
[0059] Figure 2 The XRD spectrum of the oxygen-deficient nano zinc oxide particles obtained in this example is obtained by X-ray powder diffraction. The spectrum can show that the final product is a nano-sized zinc oxide material. At the same time, through the Gaussian fitting spectrum, it can be seen that the unit cell parameters are reduced relative to the standard zinc oxide, which proves the existence of oxygen defects in the nano-sized zinc oxide material.
[0060] Fig.12 This is the XPS characterization result of this embodiment, which shows that the defect component content of the oxygen-rich defect nano zinc oxide particles of this embodiment accounts for 47.6%.
[0061] Fig.13 It is the EPR characterization result of this example, which shows that the oxygen-rich defect nano zinc oxide particles of this example have a large number of unpaired electrons. The two characterizations simultaneously prove that Example 1 has a large number of oxygen-rich defect nano zinc oxide particles with defect sites.
[0062] Table 1 Comparison of lattice constants and crystal sizes of oxygen-defective nano zinc oxide particles
[0063]
[0064] Example 2
[0065] A method for preparing oxygen-rich defective nano zinc oxide particles comprises the following steps:
[0066] Step 1: 814 mg of zinc oxide, 5.04 g of oxalic acid dihydrate and 2 mL of 1,4-diamine are dissolved in 20 mL of deionized water in sequence, and mixed evenly to prepare 21 mL of a zinc-containing precursor solution.
[0067] Step 2: Heat the zinc-containing precursor solution to 130° C. in a sealed environment and keep the temperature for 24 hours. Centrifuge at 8000 rpm to obtain a crude product, wash the crude product four times with 20 mL of deionized water, and dry to obtain 2.30 g of zinc-containing MOF solid particles.
[0068] Step 3, placing the zinc-containing MOF solid particles in a tube furnace preheated to 600°C, and maintaining the vacuum degree in the tube furnace at above 0.99 bar, and keeping the temperature for 1 hour to obtain 812 mg of oxygen-defective nano zinc oxide particles. Table 1 shows that after the zinc oxide particles were treated with TOPAS3, the crystal size obtained was 13.7 nm.
[0069] Figure 3 The XRD spectrum of the oxygen-deficient nano zinc oxide particles obtained in this example is obtained by X-ray powder diffraction.
[0070] Example 3
[0071] A method for preparing oxygen-rich defective nano zinc oxide particles comprises the following steps:
[0072] Step 1: 814 mg of zinc oxide, 5.04 g of oxalic acid dihydrate and 1 mL of 1,4-diamine are dissolved in 30 mL of deionized water in sequence, and mixed evenly to prepare 31 mL of a zinc-containing precursor solution.
[0073] Step 2: Heat the zinc-containing precursor solution to 130° C. in a sealed environment and keep the temperature for 24 hours. Centrifuge at 8000 rpm to obtain a crude product, wash the crude product four times with 20 mL of deionized water, and dry to obtain 2.26 g of zinc-containing MOF solid particles.
[0074] Step 3, the zinc-containing MOF solid particles were placed in a tube furnace preheated to 520°C, and the vacuum degree in the tube furnace was maintained above 0.99 bar, and the reaction was kept warm for 1 hour to obtain 812 mg of oxygen-defective nano zinc oxide particles. Table 1 shows that the zinc oxide particles were treated with TOPAS3 and the crystal size obtained was 16.5 nm.
[0075] Figure 4 The XRD spectrum of the oxygen-deficient nano zinc oxide particles obtained in this example is obtained by X-ray powder diffraction.
[0076] Example 4
[0077] A method for preparing a catalyst using oxygen-defect nano zinc oxide particles as a carrier comprises the following steps:
[0078] Step 1: Take 50 mg of the oxygen-deficient nano zinc oxide particles obtained in Example 1 and 3.7 mg of potassium hexachloropalladium IV acid, and load the potassium hexachloropalladium IV acid on the oxygen-deficient nano zinc oxide particles to obtain a palladium-based precursor salt.
[0079] Step 2: dissolving the above palladium-based precursor salt in 100 mL of diethylene glycol solvent and mixing them evenly to obtain a palladium-based precursor solution.
[0080] Step 3, heat the palladium-based precursor solution to 220°C, react for 10 minutes, and obtain a black suspension. After separating the solid crude product through a 9000rpm high-speed centrifuge, dissolve it in 20mL of ethyl acetate, wash it three times with 5mL of petroleum ether, remove the excess diethylene glycol solvent, and then dry it in an oven at 60°C to obtain 51mg of a catalyst with oxygen-defective nano zinc oxide particles as a carrier.
[0081] Figure 5 50 mg of the catalyst obtained in this example was placed in an exhaust gas catalytic purification reactor for exhaust gas purification activity testing. The exhaust gas pollutants NO x The conversion rate changes with temperature, and the exhaust pollutant NO is obtained. x The temperature at which the conversion rate is 50% (T 50 ) is 280°C. Compared with the existing catalysts with aluminum oxide, zinc oxide, titanium oxide and other materials as carriers, the exhaust pollutant NO x The temperature at which the conversion rate is 50% (T 50 ) is lower, that is, the catalytic activity is higher at relatively low temperatures.
[0082] The device for testing the exhaust gas purification activity in this embodiment is as follows Figure 1 As shown in the figure, the specific test method is as follows: at room temperature, take 50 mg of the prepared catalyst and place it in the middle of the experimental device, and fix it with 600 mg of quartz wool interlayer. The mass of palladium metal is 0.5 mg. After preheating the experimental device to 200 ° C, pass H2 200 mL / min for half an hour to complete the activation. After the device is cooled to room temperature, pass automobile exhaust simulation gas NO at the upper end of the device. x 20 mL / min, CO 20 mL / min and carrier gas Ar 200 mL / min. Then the gradient heating method was used to test NO at different temperatures. x Changes in content.
[0083] Example 5
[0084] A method for preparing a catalyst using oxygen-defect nano zinc oxide particles as a carrier comprises the following steps:
[0085] Step 1: Take 50 mg of the oxygen-deficient nano zinc oxide particles obtained in Example 2 and 3.7 mg of potassium hexachloropalladium IV acid, and load the potassium hexachloropalladium IV acid on the oxygen-deficient nano zinc oxide particles to obtain a palladium-based precursor salt.
[0086] Step 2: dissolving the above palladium-based precursor salt in 100 mL of diethylene glycol solvent and mixing evenly to obtain a palladium-based precursor solution.
[0087] Step 3, heat the palladium-based precursor solution to 220°C, react for 10 minutes, and obtain a black suspension. After separating the solid crude product through a 9000rpm high-speed centrifuge, dissolve it in 20mL of ethyl acetate, wash it three times with 5mL of petroleum ether, remove the excess diethylene glycol solvent, and then dry it in an oven at 60°C to obtain 51mg of a catalyst with oxygen-defective nano zinc oxide particles as the carrier.
[0088] Figure 6 50 mg of the catalyst obtained in this example was placed in an exhaust gas catalytic purification reactor, and the exhaust gas pollutants NO x The conversion rate varies with temperature, and the obtained T 50 Basically the same as Example 4 ( Fig. 9 shown).
[0089] Example 6
[0090] A method for preparing a catalyst using oxygen-defect nano zinc oxide particles as a carrier comprises the following steps:
[0091] Step 1: Take 50 mg of the oxygen-deficient nano zinc oxide particles obtained in Example 3 and 3.7 mg of potassium hexachloropalladium IV acid, and load the potassium hexachloropalladium IV acid on the oxygen-deficient nano zinc oxide particles to obtain a palladium-based precursor salt.
[0092] Step 2: dissolving the above palladium-based precursor salt in 100 mL of diethylene glycol solvent and uniformly mixing to obtain a palladium-based precursor solution.
[0093] Step 3, heat the palladium-based precursor solution to 220°C, react for 10 minutes, and obtain a black suspension. After separating the solid crude product through a 9000rpm high-speed centrifuge, dissolve it in 20mL of ethyl acetate, wash it three times with 5mL of petroleum ether, remove the excess diethylene glycol, and then dry it in an oven at 60°C to obtain 51mg of a catalyst with oxygen-defective nano zinc oxide particles as the carrier.
[0094] Figure 750 mg of the catalyst obtained in this example was placed in an exhaust gas catalytic purification reactor, and the exhaust gas pollutants NO x The conversion rate varies with temperature, and the obtained T 50 Basically the same as Example 4 ( Fig. 9 shown).
[0095] Example 7
[0096] A method for preparing oxygen-rich defective nano zinc oxide particles comprises the following steps:
[0097] Step 1: Dissolve 974 mg of zinc sulfide, 5.04 g of oxalic acid dihydrate and 1 mL of 1,4-diamine in 20 mL of deionized water in sequence, mix well and prepare 21 mL of a zinc-containing precursor solution.
[0098] Step 2: Heat the zinc-containing precursor solution to 130° C. in a sealed environment and keep the temperature for 24 hours. Centrifuge at 8000 rpm to obtain a crude product, wash the crude product four times with 20 mL of deionized water, and dry to obtain 2.31 g of zinc-containing MOF solid particles.
[0099] Step 3, placing the zinc-containing MOF solid particles in a tubular furnace preheated to 550° C., maintaining the vacuum degree in the tubular furnace at above 0.99 bar, and keeping the temperature for reaction for 1 hour to obtain 812 mg of oxygen-defect nano zinc oxide particles.
[0100] The oxygen-defect nano zinc oxide particles were loaded with 1 wt% of palladium metal according to the method of Example 4 to prepare oxygen-defect nano zinc oxide particle catalysts. 50 mg of the catalyst was placed in a reactor to measure NO x The conversion rate changes with temperature, and T 50 Basically the same as Example 4.
[0101] Example 8
[0102] A method for preparing oxygen-rich defective nano zinc oxide particles comprises the following steps:
[0103] Step 1: Dissolve 1009 mg of zinc chloride, 5.04 g of oxalic acid dihydrate and 2 mL of 1,4-diamine in 20 mL of deionized water in sequence, mix well and prepare 21 mL of a zinc-containing precursor solution.
[0104] Step 2: Heat the zinc-containing precursor solution to 130° C. in a sealed environment and keep the temperature for 24 hours. Centrifuge at 8000 rpm to obtain a crude product, wash the crude product four times with 30 mL of deionized water, and dry to obtain 2.28 g of zinc-containing MOF solid particles.
[0105] Step 3, placing the zinc-containing MOF solid particles in a tubular furnace preheated to 550° C., maintaining the vacuum degree in the tubular furnace at above 0.99 bar, and keeping the temperature for reaction for 1 hour to obtain 812 mg of oxygen-defect nano zinc oxide particles.
[0106] The oxygen-defect nano zinc oxide particles were loaded with 1 wt% of palladium metal according to the method of Example 4 to prepare oxygen-defect nano zinc oxide particle catalysts. 50 mg of the catalyst was placed in a reactor to measure NO x The conversion rate changes with temperature, and T 50 Basically the same as Example 4.
[0107] Example 9
[0108] A method for preparing oxygen-rich defective nano zinc oxide particles comprises the following steps:
[0109] Step 1: 814 mg of zinc oxide, 5.4 g of malonic acid and 2 mL of 1,4-butanediamine are dissolved in 10 mL of deionized water in sequence, and mixed evenly to prepare 11 mL of a zinc-containing precursor solution.
[0110] Step 2: Heat the zinc-containing precursor solution to 130° C. in a sealed environment and keep the temperature for 24 hours. Centrifuge at 8000 rpm to obtain a crude product, wash the crude product four times with 40 mL of deionized water, and dry to obtain 2.26 g of zinc-containing MOF solid particles.
[0111] Step 3, placing the zinc-containing MOF solid particles in a tubular furnace preheated to 550° C., maintaining the vacuum degree in the tubular furnace at above 0.99 bar, and keeping the temperature for reaction for 1 hour to obtain 812 mg of oxygen-defect nano zinc oxide particles.
[0112] The oxygen-defect nano zinc oxide particles were loaded with 1 wt% of palladium metal according to the method of Example 4 to prepare oxygen-defect nano zinc oxide particle catalysts. 50 mg of the catalyst was placed in a reactor to measure NO x The conversion rate changes with temperature, and T 50 Basically the same as Example 4.
[0113] Example 10
[0114] A method for preparing oxygen-rich defective nano zinc oxide particles comprises the following steps:
[0115] Step 1: 814 mg of zinc oxide, 5 g of acetic anhydride and 2 mL of 1,4-diamine are dissolved in 20 mL of deionized water in sequence, and mixed evenly to prepare 21 mL of a zinc-containing precursor solution.
[0116] Step 2: Heat the zinc-containing precursor solution to 130° C. in a sealed environment and keep the temperature for 24 hours. Centrifuge at 8000 rpm to obtain a crude product, wash the crude product four times with 25 mL of deionized water, and dry to obtain 2.29 g of zinc-containing MOF solid particles.
[0117] Step 3, placing the zinc-containing MOF solid particles in a tubular furnace preheated to 550° C., maintaining the vacuum degree in the tubular furnace at above 0.99 bar, and keeping the temperature for reaction for 1 hour to obtain 812 mg of oxygen-defect nano zinc oxide particles.
[0118] The oxygen-defect nano zinc oxide particles were loaded with 1 wt% of palladium metal according to the method of Example 4 to prepare oxygen-defect nano zinc oxide particle catalysts. 50 mg of the catalyst was placed in a reactor to measure NO x The conversion rate changes with temperature, and T 50 Basically the same as Example 4.
[0119] Comparative Example 1
[0120] This comparative example provides a method for preparing a catalyst using defect-free alumina as a carrier, comprising the following steps:
[0121] Step 1, take 50 mg of γ-alumina, 3.7 mg of potassium hexachloropalladium IV and 100 mL of diethylene glycol and mix them evenly to obtain a precursor solution.
[0122] Step 2, heat the precursor solution to 220°C, react for 10 minutes, and obtain a black suspension. After separating the solid through a 9000rpm high-speed centrifuge, dissolve it in ethyl acetate, wash it with petroleum ether to remove excess diethylene glycol, and then dry it to obtain 51 mg of a catalyst with aluminum oxide as the carrier.
[0123] 50 mg of the catalyst obtained in this comparative example was placed in an exhaust gas catalytic purification reactor. x The conversion rate changes with temperature ( Figure 8 , Fig. 9 As shown), we get T 50 is 330℃.
[0124] Comparative Example 2
[0125] This comparative example provides a method for preparing a defect-free nano zinc oxide material, comprising the following steps:
[0126] Step 1: 814 mg of zinc oxide, 2.52 g of oxalic acid dihydrate and 1 mL of 1,4-diamine are dissolved in deionized water in sequence, and mixed evenly to prepare 11 mL of a precursor solution.
[0127] Step 2: The precursor solution is sealed and heated to 130° C., and kept warm for 24 hours, then centrifuged and washed four times with deionized water, and dried to obtain a zinc-containing MOF precursor.
[0128] Step 3: Place the zinc-containing MOF precursor in a tube furnace preheated to 370° C. and react for 1 h under atmospheric atmosphere to obtain 810 mg of white defect-free nano zinc oxide material.
[0129] Fig.10 As shown, the defect-free nano zinc oxide material obtained in this comparative example was loaded with 1 wt% palladium metal according to the method of Example 4 to prepare a defect-free nano zinc oxide catalyst. 50 mg of the catalyst was taken into a reactor to measure NO x The conversion rate changes with temperature, and T 50 It is basically the same as Comparative Example 1.
[0130] Fig.13 The EPR characterization results of this comparative example are shown in FIG. 4 , from which it can be further reflected that the nano zinc oxide particles obtained in Example 1 have oxygen defects.
[0131] Comparative Example 3
[0132] This comparative example provides a method for preparing a defect-free nano zinc oxide material, comprising the following steps:
[0133] Step 1: 814 mg of zinc oxide, 2.52 g of oxalic acid dihydrate and 1 mL of 1,4-butanediamine were mixed with water to prepare 11 mL of a precursor solution.
[0134] Step 2: The precursor solution is sealed and heated to 130° C. to react for 24 hours, then centrifuged and washed four times with deionized water, and dried to obtain a zinc-containing MOF precursor.
[0135] Step 3, placing the zinc-containing MOF precursor in a tube furnace preheated to 400° C. and reacting it under atmospheric atmosphere for 1 h to obtain 809 mg of white defect-free nano zinc oxide material.
[0136] Fig.11 As shown, the defect-free nano zinc oxide material obtained in this comparative example was loaded with 1 wt% palladium metal according to the method of Example 4 to prepare a defect-free nano zinc oxide catalyst. 50 mg of the catalyst was placed in a reactor to measure NO x The conversion rate changes with temperature, and T 50 It is basically the same as Comparative Example 1.
[0137] Comparative Example 4
[0138] This comparative example provides a method for preparing a defect-free nano zinc oxide material, comprising the following steps:
[0139] Step 1: 814 mg of zinc oxide, 2.52 g of oxalic acid dihydrate and 1 mL of 1,4-diamine are dissolved in deionized water in sequence, and mixed evenly to prepare 11 mL of a precursor solution.
[0140] Step 2: The precursor solution is sealed and heated to 130° C. to react for 24 hours, then centrifuged and washed four times with deionized water, and dried to obtain a zinc-containing MOF precursor.
[0141] Step 3: Place the zinc-containing MOF precursor in a tube furnace preheated to 500° C. and react for 1 h under atmospheric atmosphere to obtain 805 mg of white defect-free nano zinc oxide material.
[0142] The defect-free nano zinc oxide material obtained in this comparative example was loaded with 1 wt% palladium metal according to the method of Example 4 to prepare a defect-free nano zinc oxide catalyst. 50 mg of the catalyst was placed in a reactor to measure NO x The conversion rate changes with temperature, and T 50 It is basically the same as Comparative Example 1.
[0143] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing oxygen-defect nano zinc oxide particles, characterized in that: The following steps are involved: Step 1, dissolving zinc salt, diamine organic matter and dicarboxylic acid in deionized water in sequence to obtain a zinc-containing precursor solution; the molar ratio of the zinc salt, diamine organic matter and dicarboxylic acid is 1:(0.5-2):(1.5-3); the mass ratio of the volume of the deionized water to the zinc salt is (1.25-5):1L / g; Step 2, heating the zinc-containing precursor solution obtained in step 1 to 100-200° C. and keeping the temperature for more than 6 hours to obtain a reaction solution, and then centrifuging, washing, and drying the reaction solution in sequence to obtain zinc-containing metal organic framework solid particles; Step 3, heating the zinc-containing metal organic framework solid particles obtained in step 2 to 500° C. to 800° C. in an inert atmosphere or vacuum condition, and keeping the temperature for more than 30 minutes to obtain oxygen-defective nano zinc oxide particles.
2. The method for preparing oxygen-rich defect nano zinc oxide particles according to claim 1, characterized in that: In step 1, the zinc salt is any one of zinc fluoride, zinc chloride, zinc bromide, zinc sulfate, zinc oxide, zinc sulfide or zinc nitride; The diamine organic compound is any one of ethylenediamine, diethylenediamine, propylenediamine, dipropylenediamine or butanediamine; The dicarboxylic acid is any one of oxalic acid, malonic acid or acetic anhydride.
3. The method for preparing oxygen-rich defect nano zinc oxide particles according to claim 2, characterized in that: In step 2, the insulation time is 6 to 48 hours; The centrifugation is performed by a centrifugal device with a rotation speed of 5000 to 10000 rpm; The washing is performed at least three times using deionized water with a purity of more than 99%.
4. The method for preparing oxygen-defect nano zinc oxide particles according to claim 3, characterized in that: In step 3, the gas in the inert atmosphere is argon or nitrogen with a purity of more than 99%; The vacuum condition is air with a vacuum degree of ≤1 bar; The insulation time is 30 minutes to 48 hours.
5. A method for preparing an oxygen-defective nano zinc oxide particle catalyst, characterized in that: The following steps are involved: Step 1, preparing oxygen-rich defect nano zinc oxide particles according to the preparation method of oxygen-rich defect nano zinc oxide particles according to any one of claims 1 to 4; Step 2, weighing a palladium salt and mixing it with the oxygen-deficient nano zinc oxide particles prepared in step 1 to obtain a palladium-based precursor salt; the palladium loading in the palladium-based precursor salt is 1 to 10 wt%; Step 3, dissolving a palladium-based precursor salt in a polyol solvent to obtain a palladium-based precursor solution; the mass ratio of the volume of the polyol solvent to the oxygen-defective nano zinc oxide particles is (0.1-1): 1 L / g; Step 4, heating the palladium-based precursor solution to 220-250° C. and keeping the temperature for more than 10 minutes, and then centrifuging, washing, and drying in sequence to obtain an oxygen-defective nano zinc oxide particle catalyst.
6. The method for preparing the oxygen-defective nano zinc oxide particle catalyst according to claim 5, characterized in that: In step 2, the palladium salt is any one of potassium hexachloropalladium IV acid, potassium hexachloropalladium IV acid, potassium tetrachloropalladium II acid, sodium hexachloropalladium IV acid, sodium tetrachloropalladium II acid or acetylacetonate palladium II.
7. The method for preparing the oxygen-defective nano zinc oxide particle catalyst according to claim 6, characterized in that: In step 3, the polyol solvent is selected from any one of diethylene glycol, pentanol, hexanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butylene glycol, dibutylene glycol or tributylene glycol with a volume concentration of 99% or more.
8. The method for preparing the oxygen-defect nano zinc oxide particle catalyst according to claim 7, characterized in that: In step 4, the insulation time is 10 to 30 minutes; The centrifugation is performed by a centrifugal device with a rotation speed of 5000 to 10000 rpm; The washing is performed using ethyl acetate with a purity of more than 99% and petroleum ether with a purity of more than 99% in sequence, and the washing is performed at least 3 times; The drying temperature is 55-65° C. and the drying time is 10-15 hours.
Citation Information
Patent Citations
Oxygen-deficient gray zinc oxide as well as preparation method and application thereof
CN113582218A